Multi-Perspective Approach to Identify Strategic Issues: A Case Study of Traditional Market Management at West Java - Arip Rahman Sudrajat; Edi Setiawan; Fepi Febianti; Rika Kusdinar; Lalas Sulastri (Iapa Proceedings Conference, 2019)
Traditional market management requires a precise and measurable system given the important role of the market in supporting the local economy on the one hand, and the complexity of the problems to be faced on the other. Efforts are needed to ensure a targeted traditional market management system, among which is oriented towards the identification and stewardship of appropriate strategic issues. This qualitative research is carried out to apply a multi-perspective approach that is considered accommodative to the variety of variables, in mapping the strategic value of various problems that arise in the management of traditional markets. The research was conducted in the traditional markets of Bantarujeg, West Java and produced strategic mapping of problem groups related to administrative, financial, organizational and traditional market development.